If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(7 + -5(6 + -1z)) + -7 = 7(5(7z + -6) + 4) + -50 5(7 + (6 * -5 + -1z * -5)) + -7 = 7(5(7z + -6) + 4) + -50 5(7 + (-30 + 5z)) + -7 = 7(5(7z + -6) + 4) + -50 Combine like terms: 7 + -30 = -23 5(-23 + 5z) + -7 = 7(5(7z + -6) + 4) + -50 (-23 * 5 + 5z * 5) + -7 = 7(5(7z + -6) + 4) + -50 (-115 + 25z) + -7 = 7(5(7z + -6) + 4) + -50 Reorder the terms: -115 + -7 + 25z = 7(5(7z + -6) + 4) + -50 Combine like terms: -115 + -7 = -122 -122 + 25z = 7(5(7z + -6) + 4) + -50 Reorder the terms: -122 + 25z = 7(5(-6 + 7z) + 4) + -50 -122 + 25z = 7((-6 * 5 + 7z * 5) + 4) + -50 -122 + 25z = 7((-30 + 35z) + 4) + -50 Reorder the terms: -122 + 25z = 7(-30 + 4 + 35z) + -50 Combine like terms: -30 + 4 = -26 -122 + 25z = 7(-26 + 35z) + -50 -122 + 25z = (-26 * 7 + 35z * 7) + -50 -122 + 25z = (-182 + 245z) + -50 Reorder the terms: -122 + 25z = -182 + -50 + 245z Combine like terms: -182 + -50 = -232 -122 + 25z = -232 + 245z Solving -122 + 25z = -232 + 245z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-245z' to each side of the equation. -122 + 25z + -245z = -232 + 245z + -245z Combine like terms: 25z + -245z = -220z -122 + -220z = -232 + 245z + -245z Combine like terms: 245z + -245z = 0 -122 + -220z = -232 + 0 -122 + -220z = -232 Add '122' to each side of the equation. -122 + 122 + -220z = -232 + 122 Combine like terms: -122 + 122 = 0 0 + -220z = -232 + 122 -220z = -232 + 122 Combine like terms: -232 + 122 = -110 -220z = -110 Divide each side by '-220'. z = 0.5 Simplifying z = 0.5
| 35000+1680.00=300440.00 | | 3x^2-3-5=5 | | z^2-i*2-2z=0 | | 175000+550.00x=35000+1680.00x | | a(x+y)=x-y | | 5x^2+x-1/10=0 | | 2/3x=-1/6 | | 7-3q=46 | | 2x+3y+x= | | iz^2-5-2z=0 | | 3x+(7/3)=(x-1) | | 10x-4=8x+24 | | x+x-2+x-5=42 | | 6x^2+77x+121=0 | | -1/x | | x+(x-2)+(x-5)=42 | | 3/8+5/6s=2/3 | | f(x)=-x^2+2x-1 | | M+3/8=40/60 | | 2x^2+3x=90 | | 2+5c-14=-4 | | 7y-3=3(2-y) | | 6x^3+18x^2-108x=0 | | 2c-3+8=3c-8 | | 3z^2-2iz+7=0 | | x^4*x^5= | | -7x-8=-6x+14 | | -7x-8=6x+14 | | -x+6-5x=14.2x | | -5x+11=21 | | -7(-x+4)=-20-x | | 3x(x^2+5x+30)=0 |